Serum cystatin C as a biomarker in non-Hodgkin lymphoma and its relationship with paraoxonase 1 activity - Mirjanić-Аzaric Bosa; Mijic, Smiljana; Radic Savic, Zana; Stankovic, Sinisa; Malcic-Zanic, Dragana; Mihailovic Egeljic, Natasa; Stojisavljevic, Đorđe; ivetic, Bojana; Bogavac-Stanojevic, Natasa (Journal of Medical Biochemistry, 2026)
Background: The aim of this pilot study was to assess the potential of cystatin C (Cys C) as a biomarker in NHL and to explore its association with paraoxonase 1 (PON1) activity. Methods: The study included 44 patients with B-cell NHL and 44 healthy subjects. Cys C was measured using the Cobas e 801 analyzer (Roche Diagnostics GmbH, Mannheim, Germany), while PON1and TAS were measured on the ILab 300+ system (Instrumentation Laboratory, Milan, Italy). Results: The serum level of Cys C (mg/L) was significantly higher in NHL patients compared to control subjects :1.03 (0.88–1.24) vs 0.83 (0.78–0.90), P <0.001. The diagnostic performance of Cys C, as assessed by the area under the ROC curve (AUC), was 0.812 (95% CI: 0.732–0.902). The optimal cut-off value for Cys C was 0.870 mg/L with a sensitivity and specificity of 77.1% and 75.6%, respectively. A significant negative correlation was observed between Cys C and PON1 activity (r = –0.42, P = 0.010) in NHL patients. Conclusions: This study underscores the potential of Cys C as a biomarker in NHL. Notably, in the multivariable analysis, Cys C emerged as the only significant predictor of the disease, with each unit increase associated with an approximately threefold higher odds of NHL. Furthermore, the negative correlation between Cys C and PON1, identified for the first time in patients with NHL, may offer valuable insights for future research into the molecular mechanisms underlying this malignancy.